2015
DOI: 10.12968/ijtr.2015.22.12.573
|View full text |Cite
|
Sign up to set email alerts
|

Perceived changes to swallowing in people with Parkinson's disease

Abstract: This document may differ from the final, published version of the research and has been made available online in accordance with publisher policies. To read and/or cite from the published version of the research, please visit the publisher's website (a subscription may be required.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…rate-accuracy tradeoffs, stressed-unstressed syllable tradeoffs, increased attention to effort), especially those who are aware of their speech imprecision. This has been observed in other areas of motor control in PD, such as swallowing (Noble et al, 2015;Suntrup et al, 2013). The phenomenon has been linked to apparently sudden rapid decline when spontaneous neural reorganization reaches its limits, as well as paradoxical improvement for a period once individuals become aware of their impairment and employ compensatory techniques.…”
Section: Discussionmentioning
confidence: 93%
“…rate-accuracy tradeoffs, stressed-unstressed syllable tradeoffs, increased attention to effort), especially those who are aware of their speech imprecision. This has been observed in other areas of motor control in PD, such as swallowing (Noble et al, 2015;Suntrup et al, 2013). The phenomenon has been linked to apparently sudden rapid decline when spontaneous neural reorganization reaches its limits, as well as paradoxical improvement for a period once individuals become aware of their impairment and employ compensatory techniques.…”
Section: Discussionmentioning
confidence: 93%
“…Dysphagia is very common and a major clinical concern in patients with PD from the early stage of the disease. Poor self-awareness of the symptoms may hamper early detection and proper management in these patients [1,2,10-12]. Therefore, early intervention employing validated screening tools and instruments would be recommended from the initial stage of the disease to improve the quality of life and mortality rate of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…Poor correlation between self-report and the water swallow test for dysphagia demonstrated that the subjective measure is not a good indicator for detecting dysphagia in patients with PD [2]. Other studies using a questionnaire or instrumental test, such as a videofluoroscopic swallowing study (VFSS) or fiberoptic endoscopic evaluation of swallowing (FEES), also showed that oro-pharyngeal dysphagia emerged in more than 50% of patients with PD who reported no problem with swallow [10-12]. Therefore, a patients’ self-report or response to a simple question whether or not they have any swallowing problem can lead to an underestimation of dysphagia in patients with PD.…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Dysphagia in patients with early stages of PD can be ameliorated by implementing dopaminergic treatment during the first few years after disease onset [22]. However, dysphagia is usually underdiagnosed in these patients due to poor self-awareness of the symptoms [81,82]. Therefore, early detection and individualised intervention are crucial for improving quality of life in patients.…”
Section: Dysphagiamentioning
confidence: 99%